The use of artificial intelligence in developing students’ footwork in badminton was raised - Muhannad Nazar Kzar (Eximia, 2024)
The paper explores the impact of artificial intelligence (AI) on developing students’ footwork in the sport of badminton. It emphasizes the potential of AI in improving motor skills required for badminton and discusses the role of AI in deducing and updating knowledge and skills. The study employs an experimental approach with third-year students at a physical education college in Iraq, focusing on the use of AI techniques and devices to enhance footwork training. The paper highlights positive effects of AI-based training programs, such as promoting healthier muscle strength, improving swing technique, and enhancing communication and cooperation among students. Additionally, it discusses the potential benefits of integrating technology, such as AI, to enhance the effectiveness of footwork training in badminton. The findings indicate a high average use and reliance on AI technologies for improving athletes’ performance and suggest the need for further research to evaluate the effectiveness of these techniques and determine the most effective ways to apply them in badminton. Overall, the paper suggests that AI has the potential to significantly impact the development of footwork in badminton and improve athletes’ performance, calling for continued exploration and application of AI in sports training.